Production of 4He and 4He [bar] in Pb-Pb collisions at √sNN=2.76 TeV at the LHC - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; Pachmayer, Yvonne C.; et al. (Journal of physics. A, Mathematical and theoretical, 2018)
Results on the production of 4He and Image 1 nuclei in Pb-Pb collisions at sNN=2.76TeV in the rapidity range |y|<1, using the ALICE detector, are presented in this paper. The rapidity densities corresponding to 0-10% central events are found to be dN/dyHe4=(0.8±0.4(stat)±0.3(syst))×10−6 and Image 2, respectively. This is in agreement with the statistical thermal model expectation assuming the same chemical freeze-out temperature (Tchem=156MeV) as for light hadrons. The measured ratio of Image 3 is 1.4±0.8(stat)±0.5(syst).